INTERPERSONAL TRUST, EMPLOYEE SATISFACTION, AND EMPLOYEE LOYALTY: A SOCIAL RESEARCH STUDY - Singh, Prashant (The journal of contemporary issues in business and government, 2022)
In this study, the main objective is to examine the relationship between employee's satisfaction and quality, customer satisfaction, and productivity. Employee satisfaction is an important driver of customer satisfaction and productivity. It focuses mainly on the IT sector in Emakulam. In Emakulam district, data were gathered from workers in various fields. The purpose of this study was to determine what factors influence employee satisfaction. Our study suggests that interpersonal trust (trust in managers and trust in peers) affects employee satisfaction and, as a result, employee loyalty. The sample which was chosen for this study was 150 workers in the IT industry of Emakulam district for the purpose of testing the relationship between trust in management and trust in peers as well as satisfaction and loyalty. Using convenience sampling techniques, data was collected via standardized questionnaires. IBM SPSS Statistics was used to analyze the data further through correlation and regression. By using IBM SPSS Statistics, the regression analysis was performed and the relationships between the independent variable and dependent variable as well as the mediating effect of Employee Satisfaction were measured. Interpersonal Trust is a driver of Employee Satisfaction and, in turn, affects Employee Loyalty. As an expression of the mediation among the two variables, Employee Satisfaction plays a significant role in this analysis. In addition, the results show that Interpersonal Tmst and Employee Loyalty have a direct effect on each other.